2022
DOI: 10.1007/s10792-021-02167-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative keratometry on visual outcomes after small-incision lenticule extraction for myopia

Abstract: Purpose To investigate the relationship between preoperative keratometry (K) and postoperative refraction and compare the visual outcomes after small-incision lenticule extraction (SMILE) between preoperative flat and steep corneas. Methods This study involved 814 consecutive eyes of 409 patients who underwent SMILE. A month later, a linear regression analysis of the relationship between preoperative K and the residual spherical equivalent (SE) along with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Lee et al showed overcorrection 1 month postoperatively in the flat cornea group, but with no differences after 1 year. 11 Similarly, Luft et al showed noninferior outcomes for flat and steep corneas after SMILE. 12 In this study, all 3 groups had high efficacy and safety indexes with no significant differences between the groups and were comparable with previous studies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Lee et al showed overcorrection 1 month postoperatively in the flat cornea group, but with no differences after 1 year. 11 Similarly, Luft et al showed noninferior outcomes for flat and steep corneas after SMILE. 12 In this study, all 3 groups had high efficacy and safety indexes with no significant differences between the groups and were comparable with previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…Lee et al showed overcorrection 1 month postoperatively in the flat cornea group, but with no differences after 1 year. 11 Similarly, Luft et al showed noninferior outcomes for flat and steep corneas after SMILE. 12…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…All participants underwent comprehensive preoperative ophthalmic examinations including BCDVA measurement, with the best correction in place, using a Snellen visual acuity chart (CP-690; Nidek Co., Ltd., Gamagori Aichi, Japan), manifest and cycloplegic refraction using 1% tropicamide ophthalmic solution (Mydrax; Sina Darou, Tehran, Iran) and an auto-refractometer (Auto-Kerato-Refractometer KR-8900; Topcon Co., Tokyo, Japan), a detailed anterior segment and fundus examination using a slit lamp (Haag-Streit, Bern, Switzerland), intraocular pressure measurement (Goldmann applanation tonometer, AT-900; Haag-Streit AG, Koniz, Switzerland), pupil size measurements in mesopic luminance, and corneal topography and pachymetry performed using the Orbscan IIz topography device (Bausch and Lomb Inc., Rochester, NY, USA). According to spherical equivalent (SEQ) (sum of sphere + half the cylinder), patients were allocated to one of three subgroups: low myopia (SEQ of - 0.75 D to - 2.99 D), moderate myopia (SEQ of - 3.00 D to - 5.99 D), and high myopia (SEQ of - 6.00 D to - 9.00 D) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%